Isolation and characterization of phages ΦZC2 and ΦZC3 against carbapenem-resistant Acinetobacter baumannii, and efficacy of ΦZC3 on A549 cells - Kareem Essam; Azza G. Kamel; Bishoy Maher Zaki; Mohamed Elhadidy; Amal Ahmed Abdel Aziz; Aysam Fayed; Tamer Roshdy; Ayman El-Shibiny (Virology Journal)
Abstract Background Acinetobacter baumannii is an opportunistic pathogen and a major causative agent of hospital-acquired infections. This pathogen can acquire various antibiotic resistance genes, including those conferring resistance to last-resort antibiotics such as carbapenems. MDR A. baumannii is known to cause several infections, including pneumonia and urinary tract infections. Consequently, there is an urgent need to explore alternative therapies, and bacteriophage (phage) has emerged as a promising therapeutic approach for combating multidrug-resistant (MDR) infections. Materials and methods This study investigates the therapeutic potential of specific bacteriophages against MDR, particularly carbapenem-resistant A. baumannii, and evaluates lytic activity against 41 clinical isolates of MDR A. baumannii. The phages morphotypes were identified by transmission electron microscope. The stability of these phages was assessed under different conditions, including pH (2, 3, 4, 7, and 10–12), temperature (-80, -20, 4, 37, 50, 60, 70, and 80 oC), UV exposure (15, 30, 45, 60. 75, 90). Their antibacterial activity was also evaluated using a time-killing assay. Bacteriophage Insensitive Mutants (BIM) was assessed by MOI of 100. Genomic characterization was performed to predict protein-coding genes, life cycle, and suitability for therapeutic applications. Additionally, the safety and therapeutic efficacy of the phage were assessed using a cell viability MTT assay on adenocarcinomic human alveolar basal epithelial (A549) cells to evaluate the ability to rescue the lung cells from infection. Results Two phages, vB_AbaP_ZC2 (ΦZC2) and vB_AbaM_ZC3 (ΦZC3), were isolated from hospital wastewater in Egypt. The phages demonstrated lytic activity against 24.3% (n = 10) and 31.7% (n = 13) of the isolates, respectively. Phage ΦZC2 demonstrated high EOP values (0.75–1) against AB23 and AB26, moderate activity on AB34 and AB35 (EOP = 0.19), and low or no activity on AB10, AB24, and AB31. Similarly, phage ΦZC3 exhibited high EOP on AB24 (EOP = 1), moderate levels on AB12, AB29, and AB38, while showing low or no efficacy against the remaining tested isolates. The morphotypes of ΦZC2 and ΦZC3 are podovirus and myovirus, respectively. The two phages were amplified using a bioreactor and reached titers of approximately 10¹⁰ PFU/ml in 2 L.ΦZC2 was stable at a pH range from 3 to 12 approximately 108 PFU/ml, while ΦZC3 was stable at a pH range from 3 to 11 approximately 109 PFU/ml compared to pH 7. ΦZC2 was stable at -80, 37, and 50 °C approximately 108 PFU/ml, while ΦZC3 was stable at -80, 37,50, 60, and 70 °C with approximately 109 PFU/ml compared to 4 °C. Additionally, the ΦZC2 phage exhibited stability at 90 min, while ΦZC3 phage exhibited stability at 75 min of exposure to UV light. The optimum MOI at which the ΦZC2 and ΦZC3 significantly reduced bacterial growth 0.1 and 0.01, respectively. The BIM frequency was higher for phage ΦZC3 compared to ΦZC2, indicating a slightly greater emergence of phage-resistant mutants with ΦZC3. Whole genome sequencing and annotation did not identify markers for lysogeny or antibiotic resistance. Phylogenetic analysis classified ΦZC2 and ΦZC3 within the genera of Obolenskvirus and Friunavirus, respectively. ΦZC3 was selected for its broad host range to be evaluated for rescuing A549 cells from MDR A. baumannii infection. ΦZC3 phage was not cytotoxic to A549 cells and rescued lung cells cocultured, reducing the concentration of bacteria by approximately 5 logs with different MOIs, after 6 h of incubation. Conclusion In this study, the two lytic phages have antibacterial activity against MDR A. baumannii. particularly, ΦZC3 can be a potential therapy for pulmonary infections.